Multi-omics analysis of diabetic cardiomyopathy pathogenesis using a type 2 diabetic Zucker diabetic fatty rat model - Kazuhiro Tanabe; Qianqian Zheng; Xuguang Zhang; Naoki Tanaka; Chihiro Hayashi; Asaka Yokota; Rina Otsuka; Tomoko Katahira; Motoyuki Kohjima; Makoto Nakamuta (Scientific Reports)
Abstract Diabetic cardiomyopathy (DCM) is a leading cause of mortality in patients with diabetes, highlighting the need to better understand its mechanisms for effective treatment. The primary pathogenic mechanism of DCM is mitochondrial dysfunction associated with increased oxidative stress; however, the exact reasons why diabetes triggers this condition remain unclear. An 8-week-old male Zucker diabetic fatty rat model of type 2 diabetes was used for this analysis. Metabolomic and lipidomic analyses were conducted not only in the heart but also across several other organs to elucidate metabolic changes specifically occurring in the heart. Proteomic analysis and gene expression profiling using qPCR were performed on the heart to achieve a comprehensive understanding. The marked reduction of the radical scavenger carnosine and the increased gene expression of catalase and Sestrin2 in the heart suggested elevated oxidative stress. A decrease in Complex I proteins and an increase in Complex I gene expression indicate rapid mitochondrial turnover in diabetic cardiomyocytes. Additionally, the increased expression of adenylate kinase and xanthine oxidoreductase accelerated the adenosine monophosphate degradation pathway, leading to reactive oxygen species generation. These insights into mitochondrial dysfunction and metabolic disturbances could inform the development of innovative therapies and pharmacological approaches for managing diabetic heart failure.